Title: Molecular characterization of TatD DNase gene from Staphylococcus pasteuri RA3T - Alborzian Deh Sheikh, Amin; Hosseini, Ramin (Research in Biotechnology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–> Staphylococcus pasteuri strain RA3T a gram positive, non-spore forming, non-motile, catalase positive was isolated from surface soil. The identification of the bacterium was confirmed with 16S rDNA phylogeny and biochemical tests. TatD is shown to be a cytoplasmic protein and exhibits magnesium-dependent DNase. The TatD family has no involvement in protein export by the Tat system. A TatD DNase gene was isolated and cloned from Staphylococcus pasteuri strain RA3T genome. Nucleotide sequence analysis revealed 774 nucleotides in length encoded for a protein of 257 amino acid residues. The TatD gene showed a high similarity to homologs belongs to Staphylococcus warneri SG1. The deduced polypeptide sequence harbors a typical catalytic site, HHRPEDHRHFSSGEDPLN and its calculated molecular mass and its predicted isoelectric point are 29656.7 Da and 5.05, respectively. The deduced amino acid sequence showed a high degree of similarity to TatD DNase isoforms from Staphylococcus genus and other sources. Three dimensional predictions of TatD confirmed active site and theoretical functions as DNase. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:Arial; –> <!–[endif] –>